8
$\begingroup$

Find the value of $$1\sin 2^{\circ} +2\sin 4^{\circ} + 3\sin 6^{\circ}+\cdots+ 90\sin180^{\circ}$$

My attempt

I converted the $\sin$ functions which have arguments greater than $90^\circ$ to $\cos$ but I have gone no where with it!

I also tried using double angle formula for the angles which are even.

$\endgroup$
  • 2
    $\begingroup$ Shouldn't the first term be $\sin 2^\circ$? $\endgroup$ – Jack D'Aurizio Jul 23 '16 at 16:17
  • $\begingroup$ I also thinks first will be that $\sin2°$ $\endgroup$ – Aakash Kumar Jul 23 '16 at 16:23
  • $\begingroup$ Yes you are right...I will fix it $\endgroup$ – sidt36 Jul 23 '16 at 16:27
30
$\begingroup$

An approach. One may write $$ \begin{align} \sum_{k=1}^nk\sin(ka)&=\sum_{k=1}^n\frac{d}{da}(-\cos(ka)) \\\\&=-\frac{d}{da}\sum_{k=0}^n\cos(ka) \\\\&=-\frac{d}{da}\left(\frac{1}{2}+\frac{\sin\left[(n+\frac12)a\right]}{2\sin \frac a2} \right) \\\\&=\frac{(n+1) \sin(na)-n \sin((n+1)a)}{4\sin^2 \frac a2} \end{align} $$ then one may take $a:=2^{\circ}, \, n:=90$.

$\endgroup$
8
$\begingroup$

Hints: Your sum is related with: $$ S=\sum_{n=1}^{90} n \sin\left(\frac{\pi n}{90}\right) = \sum_{n=0}^{89}(90-n)\sin\left(\frac{\pi n}{90}\right)\tag{1}$$ that fulfills: $$ \color{red}{2\,S} = 90\sum_{n=1}^{89}\sin\left(\frac{\pi n}{90}\right) = \color{red}{90\cdot\cot\left(\frac{\pi}{180}\right)}.\tag{2}$$

$\endgroup$
5
$\begingroup$

Use $\sin(\theta)=\sin(180^\circ-\theta)$. Let the summation as $S$. Then \begin{align} 2S&=\sum_{k=1}^{90}(k\sin(2k^\circ)+(90-k)\sin((180-2k)^\circ)) \\ &=90\sum_{k=1}^{90}\sin(2k^{\circ}) \end{align} Now use $-2\sin(2k^\circ)\sin(1^\circ)=\cos((2k+1)^\circ)-\cos((2k-1)^\circ)$, then \begin{align} S=45\sum_{k=1}^{90}\sin(2k^{\circ})=-\frac{45}{2\sin(1^\circ)}\sum_{k=1}^{90}(\cos((2k+1)^\circ)-\cos((2k-1)^\circ)=\frac{45\cos(1^\circ)}{\sin(1^\circ)}=45\cot(1^\circ) \end{align}

$\endgroup$
  • 2
    $\begingroup$ $\sin x \geq 0, \; \forall x\in [0^{\circ},180^{\circ}]$ $\endgroup$ – Ng Chung Tak Jul 23 '16 at 16:25
  • $\begingroup$ @NgChungTak I edited. Thanks. $\endgroup$ – Seewoo Lee Jul 23 '16 at 16:53
5
$\begingroup$

$$\sin\theta=\sin(\pi-\theta)$$

$$\sin 2^{\circ} +2\sin 4^{\circ} + 3\sin 6^{\circ}\cdots 88\sin4^{\circ}+89\sin 2^{\circ}+ 90\sin 0^{\circ}$$

$$90(\sin 2^{\circ} +\sin 4^{\circ} + \sin6 ^{\circ}\cdots \sin 90^{\circ}) -45\sin90^{\circ} $$

Now it is easy to evaluate this sum .

$\sin \alpha +\sin (\alpha+\beta)+\sin (\alpha+2\beta) +\cdots n$ terms
$$=\frac{\sin{\frac{n\beta}{2}}}{\sin{\frac{\beta}{2}}}{\sin\left[ {\alpha + \frac{\beta}{2}{(n-1)}}\right]}$$

$$90\sin 45^{\circ}\left[\frac{\sin 46^{\circ}}{sin 1^{\circ}}\right] -90\sin 45^{\circ}.\cos45^{\circ}$$ $$90\sin 45^{\circ}\left[\frac{\sin 46^{\circ}}{sin 1^{\circ}} -\cos45^{\circ}\right]$$

Now it is almost done simplify it and get $$45\cot 1^{\circ} $$

$\endgroup$
  • $\begingroup$ @sidt36: how can the sum of positive numbers be zero? $\endgroup$ – Jack D'Aurizio Jul 23 '16 at 16:41
3
$\begingroup$

As a complement to other answers, you should know that the following identities are valid

$$ \begin{align} 2 \sin \frac{1}{2} x \sum_{k=1}^{n} \cos kx &= +\sin(n+\frac{1}{2})x - \sin\frac{1}{2}x \\ 2\sin \frac{1}{2} x \sum_{k=1}^{n} \sin kx &= -\cos(n+\frac{1}{2})x + \cos\frac{1}{2}x \end{align}$$

Thsese formulas can easily be proved by moving $\sin \frac{1}{2} x$ into the summation, using the identities

$$ \begin{align} 2 \sin \frac{1}{2} x \cos kx &= + \sin(k + \frac{1}{2})x - \sin(k - \frac{1}{2})x \\ 2 \sin \frac{1}{2} x \sin kx &= - \cos(k + \frac{1}{2})x + \cos(k - \frac{1}{2})x \end{align}$$

and the telescoping property of partial sums. In your example, we have

$$x=2\frac{\pi}{180}=\frac{\pi}{90}$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.